Louvre Aulos–3D Model (Musée du Louvre, inv. nr. E10962) - Lynch, T (University of Oxford, 2021)
This is a 3D model of the Louvre aulos (inv. nr. E10962), which follows the measurements published by Stefan Hagel (Hagel, S. ‘Better understanding the Louvre Aulos’, Studien zur Musikarchäologie 9, Orient-Archäologie 33, 131–142).